COMPORTAMIENTO DEL METABOLISMO LIPÍDICO EN PACIENTES CON VIH/SIDA DE BOGOTÁ - M. Guerra; V. Valbuena; V.L. Fonseca; M. Alvarado (Universitas Scientiarum)
The purpose of this study was to compare some parameters of the lipid profile: total cholesterol, triglycerides,LDL (Low-density Lipoprotein), VLDL (Very Low-density Lipoprotein), HDL (High-density lipoprotein)and the apoproteins A-I and B100, in 30 adult patients diagnosed with HIV/AIDS without previous retroviraltherapy, and 30 healthy individuals selected from ambulatory care in the San Juan de Dios Hospital inBogotá, D.C. Colombia. HIV/AIDS patients showed significant increases (p<0,05) in triglycerides andVLDL-c, compared to control patients, it was also observed that concentrations of total cholesterol, LDL-c,HDL-c, apoproteins B100 and A-I were lower in HIV/AIDS patients than in control patients group. Nosignificant differences between men and women were observed (p>0,05) inside affected cohort. It ispossible that alteration of lipid metabolism may contribute to progression of the disease observed in HIV/AIDS infection.